The non-parameter penalty function method in constrained optimal control problems. (1991) - Xing, An-Qing
Abstract : This paper is concerned with the generalization, numerical implementation and testing of the non-parameter penalty function algorithm which was initially developed for solving n -dimensional optimization problems. It uses this method to transform a constrained optimal control problem into a sequence of unconstrained optimal control problems. It is shown that the solutions to the original constrained problem. Convergence results are proved both theoretically and numerically.